Fundamental of entrepreneurship ENT300 Ethnic cafe / Pamela Utih Anak Machie... [et.al] - Machie, Pamela Utih; Albert Atal, Pauline Nara; Bunyau, Marianie Lantie; David, Madellina (2015)
The business is based on partnership where it consists of four (4) members who hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM50,000 where total contribution of each member is RM12,500 amd the rest RM50,000 is from Bank Islam’s loan. Our company named Ethnic Café with tag line ‘Chill, Drinks & Relax’ is located at Summer Mall, Kota Samarahan with address The Summer Shopping Mall (G25-27 & G98-99, Ground Floor, Zone B), 94300 Kota Samarahan, Sarawak.